Autonomous control for miniaturized mobile robots in unknown pipe networks - Nguyen, T. L.; Blight, A.; Pickering, A.; Jackson-Mills, G.; Barber, A. R.; Boyle, J. H.; Richardson, R.; Dogar, M.; Cohen, N. (Frontiers in Robotics and AI, 2022)
Despite recent advances in robotic technology, sewer pipe inspection is still limited to conventional approaches that use cable-tethered robots. Such commercially available tethered robots lack autonomy, and their operation must be manually controlled via their tethered cables. Consequently, they can only travel to a certain distance in pipe, cannot access small-diameter pipes, and their deployment incurs high costs for highly skilled operators. In this paper, we introduce an autonomous control strategy for a miniaturised mobile robot for sewer pipe inspection that is effective, stable, and requires only low-computational resources. The robots used here can access pipes as small as 100 mm in diameter. Due to their small size, low carrying capacity, and limited battery supply, our robots can only carry simple sensors (one inertia measurement unit, two wheels encoder, and three distance sensors), a small processor, and miniature wheel-legs for locomotion. Yet, our control method is able to compensate for these limitations. We demonstrate fully autonomous robot mobility in a sewer pipe network, without any visual aid or power-hungry image processing. The control algorithm allows the robot to correctly recognise each local network configuration such as straight pipe sections, T-junctions, branches, corners, dead-ends and obstacles, and to make appropriate decisions accordingly. The control strategy was tested using the physical micro robot in a laboratory pipe network. In both simulation and experiment, the robot autonomously and exhaustively explored an unknown pipe network without missing any pipe section while avoiding obstacles. This is a significant advance towards fully autonomous inspection robot systems for sewer pipe networks.